A Proposal for Testing Fuel Cell Performance Under Resistive Loads - Lê Phương Long; Nguyễn Thanh Sơn; Nguyễn Đức Duy; Đỗ Tín Đạt; Vũ Hải Đăng (Journal of Technical Education Science, 2025)
Fuel cells are a potential energy source for zero-emission vehicles due to their high efficiency and environmental friendliness. However, their implementation on real-world loads still faces significant challenges, including manufacturing technology, cost, and experimental risks. This study proposes a method to test the performance of fuel cell systems on urban vehicle models, through load levels of 10Ω, 5Ω, 2Ω, and 1Ω, corresponding to low, medium, and high current consumption levels. The load test mode is implemented for 20 minutes, in which the starting level is 20s in 1Ω mode and 240s in 10Ω, 5Ω, and 2Ω modes, respectively. The results show that the hydrogen consumption is affected by the consumed current and the system efficiency increases by 3-6% depending on the operating mode. However, during startup, the high current causes the voltage to always drop below 12V, requiring an auxiliary power source from a Li-ion battery to protect the fuel cell system. To maintain a power level that keeps the voltage close to 12V, a voltage converter is needed for the system.